1991
DOI: 10.4315/0362-028x-54.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Modified Atmosphere Packaging and Low-Dose Irradiation on Toxin Production by Clostridium botulinum in Fresh Pork

Abstract: The combined effect of three initial levels of oxygen (0, 10, and 20%), irradiation dose (0, 0.5, and 1 kGy), and storage temperature (5, 15, and 25°C) on toxin production by Clostridium botulinum in inoculated modified atmosphere packaged pork were investigated using factorial design experiments. Toxin was detected after only 2 d in all treatments stored at 25°C. At 15°C, irradiated and nonirradiated product packaged with 10 or 20% headspace oxygen were toxic after 14 d. For product packaged with 0% oxygen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…Thus, the greater the microbial counts, the quicker the oxygen consumption within the headspace of the package. Our results are similar to those obtained by Lambert et al (1991) who reported that oxygen decreased more slowly within packaged pork samples subjected to a preservation technique when compared to those not subjected to the preservation technique.…”
Section: Resultssupporting
confidence: 91%
“…Thus, the greater the microbial counts, the quicker the oxygen consumption within the headspace of the package. Our results are similar to those obtained by Lambert et al (1991) who reported that oxygen decreased more slowly within packaged pork samples subjected to a preservation technique when compared to those not subjected to the preservation technique.…”
Section: Resultssupporting
confidence: 91%
“…Even though, both Tyson and AJC marks were unpackaged at retail selling. The effect of freezing on the microorganisms may be the major reason for lowering coagulase positive staphylococcal count (Lambert et al, 1991 andJay et al, 2005). In a similar study, Al-Hamadany (2009) mentioned that the mean count of Staphylococcus aureus in Sadia mark thighs was zero CFU/ g meat in whole sells, and 1×10 2 CFU/g meat in retail sells.…”
Section: Discussionmentioning
confidence: 99%
“…(5,13,15,20). Previous studies using proteolytic C. botulinum reported a delay in neurotoxin formation with headspace con- centrations in excess of 45% CO 2 (11,12,17,18), although a further report indicated that neurotoxin formation was unaffected by sparging with 100% CO 2 (30). This apparent inconsistency probably reflects differences in experimental design.…”
Section: Resultsmentioning
confidence: 96%